MODEL CTL UNTUK MENINGKATKAN HASIL BELAJAR PELAJARAN IPA KELAS II SDN 111/IX MUHAJIRIN - Sofiah, Sofiah (JURNAL SINEKTIK, 2018)
The purpose of this research is to increase learning outcome in IPA subjects in class II. This research is a Classroom Action Research, includes: planning, implementation, and reflection, 34 study subjects consisted of 16 males and 18 females, Data collection techniques used a written assessment on the basic competence of identify beneficial and harmful living creatures, observations in the form of indicators of teacher and student success, the results showed that pre cycle of percentage of student learning outcomes that is 24%, in the first cycle increased by a percentage 71%, the highest 74, the lowerst 45, and the average 66,94, then in the second cycle is 100% complete, the highest 85, the lowest 75, and the average 81,18. Based on these results, it can be concluded that CTL model can improve the learning outcomes of grade II students in IPA subjects at elementary school number 111 / IX Muhajirin.